Article Review: Production and Purification of Antibiotics from Environmental Microorganism - Hashim, Saba Talab; Al-Taei, Saba Riad Khudhaier; Saleh, Tahreer Hadi; Al-Rubaii, Bahaa Abdullah Laftaah (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
The use for antibiotics to treat microbial with bacteria has been for decades a mainstay of contemporary therapy. Nevertheless, extensive antimicrobial abuse or trafficking has resulted in unforeseen effects that need significant policy reforms for prevention. Researchers discuss two major categories of implications of antimicrobial misuse and excess use in this review. Subsequently talk about how antibiotic resistance spreads from hotspot where resistance evolution occurs to the environment, having a focus on possible resistance dissemination channels. Furthermore, they describe how naturally occurring populations of microbes, in addition to crustaceans including vertebrate organisms are impacted by antimicrobial contamination; regardless of the development of susceptibility. Individuals conclude with a summary of the local initiatives that are now being implemented to mitigate the consequences of antimicrobial contamination as well as regions where these strategies are still being developed.